(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the problem of life and language interrelation in a context of Ludwig Vitgenschtein doctrine. Linguistic philosophy explains being and language correlation from the priority of language over thinking. The accent on the importance of idea of linguistic philosophy for a modern science, in particular for development in linguistics of the concept of the world language picture is made.